The psychological safety of the educational environment of Ukrainian higher education institutions in a pandemic: empirical data of a comparative analysis of participants' assessments studying online - Bondarchuk, Olena I.; Balakhtar, Valentyna V.; Ushenko, Yuriy O.; Gorova, Olena O.; Osovska, Iryna M.; Pinchuk, Nataliia I.; Yakubovska, Nataliia O.; Balakhtar, Kateryna S.; Moskalov, Maksym V. (Serhiy Semerikov, 2022)
This paper highlights the problem of ensuring the psychological safety of participants of the educational process in the mass transition to distance learning, caused by the complex conditions of our time and the specific features of the digital environment in the COVID-19 pandemic. The study demonstrates the results of a comparative analysis of students’ assessments studying online in a pandemic, the peculiarities of the psychological safety of the educational environment and its impact on students studying online in a pandemic. Also, this paper reveals the insufficient tendency to decrease the level of psychological safety of the educational environment for a significant number of subjects. There are statistically significant differences in the peculiarities of the psychological safety of participants in the educational process as to gender, age, and status. The survey of participants in the educational process presents the results as to their attitude to the peculiarities of learning under the conditions of the COVID-19. They testify to the deterioration of psychological safety in the educational environment of higher education institutions, and, accordingly, the subjective well-being of participants in the educational process in a pandemic. There was a decrease in the number of respondents with a positive attitude to distance learning and a willingness to work exclusively online. The study displays the expediency of full-time and distance learning as such, which is optimal for the organization of the educational process and contributes to the psychological safety of participants in the educational process.
Keywords: Psychological Safety; Participants of the Educational Process; Pandemics, Coronavirus Disease 2019; Educational Environment; Distance Learning